Large Draining Focal Fibrous Hyperplasia Secondary to Periapical Granuloma - E. I. Ogbureke; M. A. Couey; N. Vigneswaran; C. D. Johnson (Case Reports in Dentistry)
Periapical granuloma is a pathological diagnosis associated clinically and radiographically with a nonvital tooth and a periapical radiolucency, respectively. It is frequently seen as a sequela of long-standing pulpal necrosis. Often times, a draining fistula is observed near the nonvital tooth. We report an unusual case of a large draining focal fibrous hyperplasia in association with a large periapical granuloma treated at our clinic. The diagnosis was made by the clinical presentation, radiologic and histopathologic findings.